Ovariectomy-induced hormone deprivation aggravates Aβ1-42 deposition in the basolateral amygdala and cholinergic fiber loss in the cortex but not cognitive behavioral symptoms in a triple transgenic mouse model of Alzheimer’s disease - Farkas, Szidónia; Szabó, Adrienn; Török, Bibiána; Sólyomvári, Csenge; Fazekas, Csilla Lea; Bánrévi, Krisztina; Correia, Pedro; Chaves, Tiago; Zelena, Dóra (Frontiers in Endocrinology, 2022)
Alzheimer’s disease is the most common type of dementia being highly prevalent in elderly women. The advanced progression may be due to decreased hormone synthesis during post-menopause as estradiol and progesterone both have neuroprotective potentials. We aimed to confirm that female hormone depletion aggravates the progression of dementia in a triple transgenic mice model of Alzheimer’s disorder (3xTg-AD). As pathological hallmark is known to appear in 6-month-old animals; we expected to see disease-like changes in the 4-month-old 3xTg-AD mice only after hormone depletion. Three-month-old female 3xTg-AD mice were compared with their age-matched controls. As a menopause model, ovaries were removed (OVX or Sham surgery). After 1-month recovery the body composition of the animals were measured by an MRI scan. The cognitive and anxiety parameters were evaluated by different behavioral tests, modelling different aspects (Y-maze, Morris water maze, open-field, social discrimination, elevated plus maze, light-dark box, fox-odor, operant conditioning, conditioned fear test). At the end of the experiment uterus was collected, amyloid-β accumulation, and the cholinergic system in the brain was examined by immunohistochemistry. The uterus weight decreased, and the body weight increased significantly in the OVX animals. The MRI data showed that the body weight change can be due to fat accumulation. Moreover, OVX increased anxiety in control, but decreased in 3xTg-AD animals, the later genotype being more anxious by default based upon the anxiety z-score. In general, 3xTg-AD mice moved less. In relation to cognition neither the 3xTg-AD genotype nor OVX surgery impaired learning and memory in general. Despite no progression of dementia-like behavior after OVX, at histological level OVX aggravated the amyloid-β plaque deposition in the basolateral amygdala and induced early cholinergic neuronal fiber loss in the somatosensory cortex of the transgenic animals. We confirmed that OVX induced menopausal symptoms. Removal of the sexual steroids aggravated the appearance of AD-related alterations in the brain without deep worsening of the behavior. Thus, the OVX in young, 3-month-old 3xTg-AD mice might be a suitable model for testing the effect of new treatment options on structural changes, however, to reveal any beneficial effect on behavior later timepoint might be needed.